Extracting Witnesses from Proofs of Knowledge in the Random Oracle Model - Groth, Jens (BRICS Report Series, 2001)
We prove that a 3-move interactive proof system with the special soundness property made non-interactive by applying the Fiat-Shamir heuristic is almost a non-interactive proof of knowledge in the random oracle model. In an application of the result we demonstrate that the Damgård-Jurik voting scheme based on homomorphic threshold encryption is secure against a nonadaptive adversary according to Canetti's definition of multi-party computation security.